Cation Template‐Assisted RAFT Cyclopolymerization of Hexa(Ethylene Glycol) Di(meth)acrylates to Thermoresponsive Pseudo‐Crown Ether Polymers. Issue 18 (21st September 2021) - Kimura, Yoshihiko; Terashima, Takaya
Abstract : Front Cover : In article number 2000670 by Yoshihiko Kimura and Takaya Terashima, hexa(ethylene glycol) di(meth)acrylates efficiently interact with a potassium cation to dynamically form pseudo cyclic monomers. Combined with such a supramolecular technique, RAFT cyclopolymerization of hexa(ethylene glycol) di(meth)acrylates with a potassium cation template is developed to successfully synthesize cyclopolymers comprising 24‐membered hexa(ethylene glycol) rings. The cyclopolymers serve as thermoresponsive pseudo‐crown ether polymers.